DEVELOPMENT OF A LEARNING VIDEO TOOL USING THE CANVA APPLICATION ON ETHNIC AND RELIGIOUS DIVERSITY IN MY COUNTRY SUB-THEME AT GRADE IV ELEMENTARY STUDENTS - Nur Alifia Ananda; Ratih Purnamasari; Resyi A. Gani (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
This paper discusses the development of learning videos based on Canva in order to be suitable use as varied, creative, and innovative learning videos on theme 7 of sub-theme 1 learning 1 regarding ethnic and religious diversity in my country in class IV-B SDIT Asalamah. With the development of this learning video, the students become more interested and enthusiastic to learn in class. The research method used by the author is Research and Development (R&D) using the ADDIE methodology (Analysis, Design, Development, Implementation, Evaluation). Learning video media uses the Canva app, which was designed and tested by linguists with a 100% rating. It is categorized as feasible, 94% of the material expert reviews are rated feasible, and the media review test is rated 100% as very feasible. The small group test indicates an average score of 73.33% with a feasible category and the large group test implies an average score of 95.06% with a very feasible category. The results of the pretest and posttest are also produced with N-gain at 0.72, which means that the students can follow and complete the learning process properly. Thus, it can be concluded that the developed learning video media is suitable to be used by teachers and students in the learning process at SDIT Assalamah Depok.